A theory on measuring the one-way speed of light and a method of verifying the invariance of light speed - Dong, JinXi; Dong, Bo (Physics essays, 2011)
The measurement of one-way speed of light has remained an unsolved physical problem for a long time. The reason is that people were entrapped in the thinking pattern formed in low speed measurement, i.e., the one-way speed measurement relied on a synchronization signal with higher speed to synchronize the distant clock. The authors break this pattern with a new theory and experiment method, in which the light propagating in one direction is not only treated as a quantity to be measured but also as a time standard and a clock synchronization signal, which can avoid the infinite error and the logic circle of distant clock synchronization in the former method, thereby presenting the possibility to measure one-way speed of light and verify the isotropy of light speed. © 2011 Physics Essays Publication. [DOI: 10.4006/1.3579492]